2023
DOI: 10.1001/jamanetworkopen.2022.55395
|View full text |Cite
|
Sign up to set email alerts
|

Association of Modifiable Health Conditions and Social Determinants of Health With Late Mortality in Survivors of Childhood Cancer

Abstract: ImportanceAssociations between modifiable chronic health conditions (CHCs), social determinants of health, and late mortality (defined as death occurring ≥5 years after diagnosis) in childhood cancer survivors are unknown.ObjectiveTo explore associations between modifiable CHCs and late mortality within the context of social determinants of health.Design, Setting, and ParticipantsThis longitudinal cohort study used data from 9440 individuals who were eligible to participate in the St Jude Lifetime Cohort (SJLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…9,10 In survivors of childhood cancer, diabetes has been shown to potentiate the risk of heart failure in a near-multiplicative fashion 11 and increase risk of death independent of treatment exposures. 12,13 Therefore, new onset of diabetes in survivors is a critical marker identifying a high-risk state. On the basis of this knowledge, prevention of diabetes to prevent cardiovascular disease and death now becomes a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In survivors of childhood cancer, diabetes has been shown to potentiate the risk of heart failure in a near-multiplicative fashion 11 and increase risk of death independent of treatment exposures. 12,13 Therefore, new onset of diabetes in survivors is a critical marker identifying a high-risk state. On the basis of this knowledge, prevention of diabetes to prevent cardiovascular disease and death now becomes a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…4 Exercise-, diet-, and smoking cessation-based approaches may prevent and reduce some late-stage complications. 3 The International Guideline Harmonization Group found that individualized surveillance and timely intervention improve the quality of life and preserve the health of CCS. 5,8 As of 2017, more than 90% of providers affiliated with pediatric oncology groups in the United States offered long-term follow-up (LTFU) services for CCS, an increase from the 2007 survey; however, less than 75% of CCS in need of LTFU services receive those services.…”
mentioning
confidence: 99%
“…Examples of such complications include endocrine or cardiovascular dysfunction or even secondary cancers. [3][4][5] Although the mechanisms that control late-stage complications are unclear, the biological cellular senescence is likely a contributor. 6 Therefore, by the age of 50 years, almost 100% of patients who are CCS will have developed potentially life-threatening, chronic health conditions resulting in secondary organ dysfunction.…”
mentioning
confidence: 99%
See 2 more Smart Citations